Strategic Management of Human Resources on Organisational Quality - Romadhoni, Kunni Faizah; Nurfuadi, Nurfuadi (JMB : Jurnal Manajemen dan Bisnis, 2025)
Improving organizational quality is very dependent on effective human resource management. Strategic human resource management plays an important role in designing and implementing policies that support the achievement of an organization's goals. This research is based on the challenges faced by organizations in optimizing human resource potential to achieve superior performance. Human resource management includes a series of planned practices that aim to attract, develop, motivate and retain members who have qualifications according to the organization's needs. The aim of this research is to analyze how the implementation of human resource management strategies can improve organizational welfare, both in terms of operational efficiency and individual performance effectiveness. The benefits of implementing this strategy include increasing productivity, developing a positive work culture, and achieving long-term competitive advantage for the organization. It is hoped that the results of this research will provide insight for organizational managers in integrating human resource strategies to improve organizational quality.